2017
DOI: 10.1108/pijpsm-03-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Using activity-based costing and simulation to reduce cost at a police communications centre

Abstract: 1Using activity based costing and simulation to reduce cost at a Police communications centre Abstract PurposeThis study is based at a Police Force's communications centre which undertakes a vital role in receiving and processing emergency and non-emergency telephone calls from the public and other agencies. The purpose of the study is to evaluate a method for addressing the conflict between the need to reduce cost and the requirement to meet national standards in terms of a timely response to customer calls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Workload for individual officers Semi-structured focus groups Fleming and Grabosky (2009) Calls for service Greasley and Smith (2017) Calls for service Green (1984) Calls for service /service time required Groff et al 2015Calls for service / Crime prevention Heller and Markland (1970) Calls for service Systematic literature review to answer questions about effectiveness of police-mental health service models for responding to people with mental disorder and suspected offending or public safety problems. Maxfield (1982) Calls for service Mazerolle et al (2002) Calls for service / Public expectations Moore and Braga (2003) Calls for service / Crime prevention Sacks (2003) Calls for service / Crime prevention Sarac et al (1999) Calls for service Taylor and Huxley (1989) Calls for service Taylor Griffiths et al (2015) Calls for service Walley (2013) Calls for service Walley and Jennison-Phillips (2018) Need for policing and service (including failure demand)…”
Section: 'Demand' In the Literaturementioning
confidence: 99%
“…Workload for individual officers Semi-structured focus groups Fleming and Grabosky (2009) Calls for service Greasley and Smith (2017) Calls for service Green (1984) Calls for service /service time required Groff et al 2015Calls for service / Crime prevention Heller and Markland (1970) Calls for service Systematic literature review to answer questions about effectiveness of police-mental health service models for responding to people with mental disorder and suspected offending or public safety problems. Maxfield (1982) Calls for service Mazerolle et al (2002) Calls for service / Public expectations Moore and Braga (2003) Calls for service / Crime prevention Sacks (2003) Calls for service / Crime prevention Sarac et al (1999) Calls for service Taylor and Huxley (1989) Calls for service Taylor Griffiths et al (2015) Calls for service Walley (2013) Calls for service Walley and Jennison-Phillips (2018) Need for policing and service (including failure demand)…”
Section: 'Demand' In the Literaturementioning
confidence: 99%
“…The computed practical capacity is then used in TDABC calculations. In the same vein, Greasley and Smith (2017) had previously proposed to use ABC to show how costs are generated, and based on the ABC results they define different resource allocations which are analyzed using discrete event‐simulation. The authors use simulation to assess other (different from costs) system performance indicators.…”
Section: Time‐driven Activity‐based Costingmentioning
confidence: 99%
“…The ABC expansion among enterprises in the Czech Republic is currently comparable with neighbouring countries, although the extent of its use is lower. Duh [7], Greasley, Smith, [8] argue that Activity Based Costing is an effective method not only for managing costs but also for strategic decisions. It is shown that businesses that know and optimize their processes are ready for changes caused by the external environment.…”
Section: Literature Reviewmentioning
confidence: 99%